Potential regulatory approaches on the environmental impacts of photovoltaics: Expected improvements and impacts on technological innovation. (18th October 2020) - Polverini, Davide; Dodd, Nicholas; Espinosa, Nieves
Abstract: This work assesses the opportunities for technological development and innovation that may be imposed or created by environmental policy. Working within the legislative framework of European Union (EU) sustainable product policies, a study of the feasibility of four specific policy instruments (Ecodesign Directive, Energy Labelling, Green Public Procurement and the EU Ecolabel) to photovoltaic products (modules, inverters and systems) led to the identification of key performance metrics and design features. Starting from an analysis of the environmental hotspots of photovoltaic products throughout the whole life cycle (from raw material extraction to their end of life and disposal), a number of areas of attention for innovation are identified and a policy approach is proposed to tackle these aspects in regulatory terms by means, in particular, of requirements within the legal framework of the Ecodesign Directive. Abstract : ▪